Virtuelle Lebenswelten. Körper - Räume - Affekte - Tuschling, Anna (De Gruyter, 2021)
No longer opposed to our everyday life, the virtual has become an integral part of it. Virtual life-worlds are not a privileged sphere of computer culture anymore virtuality shapes the present in multiple ways. This volume investigates the theory and history of virtuality and probes its uses in different life-worlds from the perspectives of media studies, sociology, literary studies, education, psychology, and law.